2016
DOI: 10.12659/msm.897657
|View full text |Cite
|
Sign up to set email alerts
|

Curative Effects of Dendritic Cells Combined with Cytokine-Induced Killer Cells in Patients with Malignant Pericardial Effusion

Abstract: BackgroundTo determine the effects of dendritic cells (DCs) and cytokine-induced killer (CIK) cells in patients with malignant pericardial effusion.Material/MethodsAll patients underwent pericardial puncture and indwelling catheter insertion. After pericardial drainage, the 16 patients in the treatment group received an infusion of 20 mL DCs and CIK cells (>1.0×1010 cells) and 500,000 U interleukin (IL)-2 for 3 successive days. The 15 control-group patients received 30 mg/m2 cisplatin and 500,000 U IL-2 for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Trials of combined therapies showed that combination of autologous DC and cytokine-induced killer (CIK) cells to treat effusions had comparably mild side effects but only modest efficacy. 178 An anecdotal report of intrapleural administration of tumor infiltrating lymphocyte (TIL) infusion compared to traditional cisplatin therapy demonstrated a claimed but very modest greater response rate (33.3% vs 28.57%) and disease control (71.43% vs 66.67%) than MPE patients given cisplatin. 183 Certainly, local and systemic TIL therapy is an area worthy of further consideration.…”
Section: Interferon Therapymentioning
confidence: 99%
“…Trials of combined therapies showed that combination of autologous DC and cytokine-induced killer (CIK) cells to treat effusions had comparably mild side effects but only modest efficacy. 178 An anecdotal report of intrapleural administration of tumor infiltrating lymphocyte (TIL) infusion compared to traditional cisplatin therapy demonstrated a claimed but very modest greater response rate (33.3% vs 28.57%) and disease control (71.43% vs 66.67%) than MPE patients given cisplatin. 183 Certainly, local and systemic TIL therapy is an area worthy of further consideration.…”
Section: Interferon Therapymentioning
confidence: 99%
“…Clinical studies paid more attention to the patients’ quality of life after treatment. Ten studies calculated the Karnofsky score (KPS) to quantify patients' general well‐being and quality of life and 8 of them indicated higher KPS after CIK cell therapy (N. Li et al, 2019; H. Luo et al, 2016; Y. Liu et al, 2016; Lu et al, 2012; Qiu et al, 2011; H. Wang, Cui, Wang, Zhao, & Sun, 2016; Yan et al, 2015; Yu et al, 2011). Patients in other studies also achieved an improvement of the general condition in different degrees including better appetite, improved sleep, weight gain, pain relief, and so forth.…”
Section: Resultsmentioning
confidence: 99%
“…The mOS of patients that received autologous CIK cell immunotherapy was significantly prolonged by 8 months with a significantly increased 3‐year OS rate (D. Chen, Sha, et al, 2018). A study on 82 patients with advanced pancreatic cancer demonstrated significantly increased mOS, disease control rate, and 6‐, 12‐, 18‐month OS rate (Z. Wang, Liu, et al, 2016). Another study including 646 postoperative epithelial ovarian cancer patients showed a significantly higher OS rate and a favorable PFS in the CIK cell plus chemotherapy group (Y. Zhou, Chen, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…95 Other clinical trials have demonstrated that the use of CIK therapy prolongs median overall survival and has a favorable effect on progression-free survival in colon, lung, pancreatic, and ovarian cancers. [96][97][98][99] These trials demonstrate the utility of CIK cells as a form of immunotherapy while also raising questions regarding the optimal length of maintenance treatments and frequency of CIK infusions. Further studies will be needed to compare efficacy between autologous and allogeneic CIK cells.…”
Section: Cytokine-induced Killer Cells In Immunotherapymentioning
confidence: 99%